Solubility and diffusivity of H2 and CO2 in the ionic liquid [bmim][PF6]. (27th July 2015) - Barghi, Seyed Hamed; Tsotsis, Theodore T.; Sahimi, Muhammad
Abstract: We report on the measurement of the solubility and diffusivity of H2 and CO2 in the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6 ]) over the temperature range 25 °C–55 °C and for pressures of up to 10 MPa. The data were obtained using a magnetic suspension balance, a gravimetric instrument that is capable of simultaneously and accurately measuring the gas solubility and diffusivity in such liquids. To our knowledge, this is the first time that the H2 diffusivity has been measured in an ionic liquid. While solubility data for H2 have been previously reported, they vary widely. The cause for such variations is discussed as well. The diffusivity data for both H2 and CO2 follow an Arrhenius-like dependence on temperature. Highlights: H2 solubility and diffusivity in [bmim][PF6 ] were measured. CO2 solubility and diffusivity in [bmim][PF6 ] were measured. The source of widely scattered H2 solubility data in the literature has been discussed. H2 diffusivity has been measured in an ionic liquids for the first time.